Caribbean trade & investment report : strategies for recovery, renewal and reform \n (Ian Randle Publishers KingstonJM, 2010)
Analyses trade and investment issues in the macro-economic facilitating and regulatory context; looks at evolving corporate structures, strategies and practices and; strategies and approaches to enhance competitiveness; analyses the offshore financial sector.
Keywords: TRADE